The Role of Dakhwah Institutions in Facing The War of Thoughts - Ponco Dwi Satrio; Sumarta Sumarta (Penerbit Hellow Pustaka, 2025)
In the era of globalization and an unstoppable flow of information, the Muslim community faces a serious challenge in the form of an ideological war (ghazwul fikri) that undermines religious identity and beliefs through the infiltration of foreign ideologies, digital media, and secular education systems. This article aims to examine the strategic role of Islamic da'wah institutions in safeguarding the ummah from such intellectual threats. This research uses a literature study method with a descriptive qualitative approach based on scholarly references and relevant documentation. The findings reveal that da'wah institutions play a crucial role as agents of moderation, education, and reinforcement of wasathiyah (moderate) Islamic identity in society. Despite challenges such as technological adaptation, digital literacy gaps, and ideological resistance, digital-based da'wah strategies and cross-institutional collaboration have proven to be effective solutions. The implications highlight the need for institutional transformation, increased human resource capacity in da'wah, and the integration of da'wah messages with national and universal humanitarian narratives. This study recommends the development of systematic digital da'wah policies and further research on the effectiveness of da'wah narratives in shaping public opinion in the digital age. These findings offer both theoretical and practical contributions to the development of contextual and adaptive da'wah models.